Appraising and incorporating qualitative research in evidence-based practice. - Henderson R; Rheault W (Journal of Physical Therapy Education (American Physical Therapy Association, Education Section))
Background and Purpose. Evidence-based practice (EBP) is widely acknowledged to be critical in the clinical practice of physical therapy. Clinicians must be able to evaluate and synthesize all available evidence to make sound clinical decisions. Current EBP theory provides specific criteria to evaluate quantitative research; how-ever, this current theory lacks provisions for consideration and inclusion of qualitative research. Incorporating qualitative research in EBP is important as quantitative and qualitative perspectives have unique contributions to under-standing phenomena in rehabilitation and informing physical therapy practice. There is no methodology commonly available or used to include qualitative research in EBP. The purposes of this research are to: 1) review the theoretical basis and methods of EBP, 2) argue the case for including qualitative research in EBP, 3) intro-duce Decision Rules for including qualitative research in EBP, 4) introduce an appraisal instrument to evaluate the methodological rigor of qualitative research papers, and 5) present an example of clinical use of this methodology. Method/Model Description and Evaluation. To address this issue, we developed an instrument, suggested by Guba's Model of Trustworthiness of Qualitative Research, to evaluate the methodological rigor of qualitative papers; we expanded Sackett's Rules of Evidence Model to provide for representation of qualitative studies; and physical therapy students used the instrument and the expanded model in clinical decision making. Outcomes. Students and physical therapists found the appraisal instrument and the methodology straight forward, simple to use, and helpful in clinical decision making. Discussion and Conclusion. Opportunities are virtually unlimited in rehabilitation to describe and interpret phenomena with qualitative research designs. Qualitative evidence deserves consideration and inclusion in EBP. The Decision Rule methodology and the appraisal instrument presented in this paper provide a means to appraise and incorporate qualitative research in EBP.